Hubungan Bonding dan Attachment Pengasuh terhadap Kecerdasan Emosional Anak Usia Pra Sekolah - Ilhami Shofiatul Mala; Nopi Nur Khasanah; Kurnia Wijayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Background: Bonding and attachment are important aspects of emotional development. The quality of emotional relationships formed through warm and responsive interactions plays a significant role in shaping an individual’s ability to recognize, manage, and express emotions appropriately. However, variations in the quality of bonding and attachment may influence the level of emotional intelligence. Methods: This study employed a quantitative research design with a correlational approach and a cross-sectional method. The sample consisted of 50 respondents selected according to the research criteria. Data were collected using questionnaires that had been tested for validity and reliability. Data analysis included validity testing, reliability testing, normality testing, and correlation testing. Since the data were not normally distributed, the relationship between variables was analyzed using the Spearman’s Rho correlation test. Results: The results showed a positive and significant relationship between bonding and emotional intelligence, with a correlation coefficient of 0.453 and a significance value of 0.001. Attachment also demonstrated a positive and significant relationship with emotional intelligence, with a correlation coefficient of 0.479 and a significance value of 0.000. Both relationships were categorized as moderate correlations. Conclusion: Bonding and attachment have a positive and significant relationship with emotional intelligence.